Immunohistochemical Study of CA 125 in Surface Epithelial Tumors of Ovary in Correlation with Serum Levels - Pillarisetty, Karishma; Ravindra, Savithri (Annals of Pathology and Laboratory Medicine, 2020)
Background: Ovarian carcinoma is the 4th leading cancer among women in India. Primary ovarian neoplasms exhibit a wide range of histopathological patterns and tumors with epithelial differentiation are most frequent. Among malignant tumors, most common histological type is serous adenocarcinoma whose diagnosis is established in advanced stages of disease in approximately 75% of patients. The most widely used tumor marker in ovarian cancer, often considered â€œgold standardâ€ is Cancer Antigen125. Cancer Antigen 125 is a high molecular weight glycoprotein which is raised in approximately 90% of patients with advanced epithelial ovarian cancer. Methods: A 2 year prospective study included 81 cases of ovarian neoplasms with surface epithelial differentiation. The specimens were fixed in 10% formalin, routinely processed. Sections of 4-5 microns thickness were obtained from the paraffin block and stained with Hematoxylin & Eosin. The tumors were categorised according to WHO classification. Immunohistochemical analysis of Cancer Antigen 125 was done in all malignant & borderline tumors. Result: A total of 81 cases were studied. There were 15 cases with elevated serum Cancer Antigen 125 levels. Of these 8 showed positive tissue expression. The sensitivity of serum Cancer Antigen 125 was 68.75% & its specificity was 93.8%. Conclusion: Serum Cancer Antigen 125 is elevated in ovarian tumors especially in malignant surface epithelial tumors & more commonly in serous cystadenocarcinoma. There was a good correlation between serum levels & tissue expression of Cancer Antigen 125.